PERANCANGAN SISTEM INFORMASI PENGELOLAAN PIUTANG PADA KOPERASI MBK MENGGUNAKAN METODE UMUR PIUTANG - Setiadi, Teguh; Ayu Hardianti, Sekar (Journal of Computer Science and Technology (JCS-TECH), 2023)
In the era of the digital economy, information systems are expected to provide an active role in terms of information. This has required a company to have an appropriate information system, in order to facilitate the process of reporting the information itself. One of the financial reports is a profit and loss report, balance sheet, changes in capital, cash flow, besides that for trading companies they also make accounts receivable reports or credit sales reports. Where accounts receivable is one of the activities that occur when a company sells products or services to consumers and consumers do not directly make payments. It can be said that receivables are one of the most crucial activities in a company. Impeded receivables can result in difficulties for the company in managing or carrying out the company’s operational activities. Therefore, it is necessary to need an information system that can manage and produce reports of late installment receivables. So, the company’s business processes can run and compete as they should.